The impact of regulation-driven environmental innovation on innovation success and firm performance - Klaus Rennings; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The impact of environmental innovations on firm performance is ambiguous. On the one hand, regulatory-driven environmental innovation may impose additional costs to firms and lower their profits. On the other hand, eco-innovators could profit from lower uncertainty in innovation due to regulatory standards and demand-generating effects of regulation. In this paper we analyse (a) whether regulation-driven environmental innovation generate similar innovation success compared to other types of product and process innovation, and (b) whether regulation-driven environmental innovation increase or decrease firm success (as measured by return on sales). Using firm data from the German innovation survey, we find that both product and process innovations driven by environmental regulation generate similar success in terms of sales with new products and cost savings as other innovations do. However, we find different effects when looking on the field of environmental regulation that triggered innovations. Regulations in favour of sustainable mobility contribute to higher sales with market novelties while regulations in the field of water management lower this type of innovation success. With regard to a firm's price-cost margin, new processes implemented in order to comply with environmental regulation requirements lower profitability, indicating higher costs for this type of innovation which cannot be passed on prices. Higher profit margins can be observed for firms with innovations triggered by regulations on recycling and waste management as well as on resource efficiency.
Keywords: Q55; Q58; L51; O31; L25; 330; Umwelttechnik; Innovation; Umweltauflage; Wirkungsanalyse; Unternehmensentwicklung; Return on Investment; Erfolgsfaktor; Schätzung; Deutschland